Mapping of soil degradation potential in Nguntoronadi District Wonogiri Regency. Issue 1 (November 2021) - Azis, A A A; Mujiyo; Cahyono, O
Abstract: Soil is the most important component in agriculture. Soil degradation is caused by improper soil management, unpatterned planting, and homogeneous rainfall. Mapping of potential soil degradation was a process of identifying initial conditions to determine areas that have the potential in soil physical, chemical, and biological degradation. The purpose of this study was to create a map of Soil Degradation Potency (SDP). The research was conducted in Nguntoronadi district, Wonogiri. The mapping used a guided-qualification method and was assisted by ArcGIS application for overlaying the maps according to standard procedures, and the resulting value of soil degradation potency. The results showed the soil degradation potency was slightly in 454 hectares, moderate in 5, 186 hectares, and high in 192 hectares. The research area was dominated by moderate to high degradation. Land management requires more attention according to soil conservation and sustainability. Further research is needed to determine the actual level of soil degradation to obtain recommendations for sustainable land management.